Fluid dynamics and dynamos in astrophysics and geophysics : reviews emerging from the Durham Symposium on Astrophysical Fluid Mechanics, July 29 to August 8, 2002 /: reviews emerging from the Durham Symposium on Astrophysical Fluid Mechanics, July 29 to August 8, 2002. (©2005) - Unknown
No abstract available